2016
DOI: 10.1111/trf.13495
|View full text |Cite
|
Sign up to set email alerts
|

How do we transfuse blood components in cirrhotic patients undergoing gastrointestinal procedures?

Abstract: The liver plays a pivotal role in hemostasis. Consequently, patients with cirrhosis frequently demonstrate abnormal coagulation profiles on routine laboratory tests. These tests mainly reflect decreased procoagulant proteins. However, in cirrhosis, complex changes also occur in anticoagulant and fibrinolytic pathways. Recent evidence demonstrates that patients with cirrhosis exist in a state of hemostatic rebalance. Accordingly, routine tests inadequately represent hemostatic alterations in these patients. Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
(154 reference statements)
0
10
0
Order By: Relevance
“…The liver is an important hematologic organ that synthesizes or eliminates several factors related to hemostasis and thrombosis. Patients with liver cirrhosis are prone to coagulopathy due to increased portal pressure and dysfunction of coagulation factors [ 27 , 28 , 29 ]. This makes liver specialists and endoscopists cautious when performing invasive procedures in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is an important hematologic organ that synthesizes or eliminates several factors related to hemostasis and thrombosis. Patients with liver cirrhosis are prone to coagulopathy due to increased portal pressure and dysfunction of coagulation factors [ 27 , 28 , 29 ]. This makes liver specialists and endoscopists cautious when performing invasive procedures in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is challenging to accurately predict the clotting status of patients with cirrhosis simply using the prothrombin time and platelet count [ 27 , 28 , 29 ]. Our study showed no difference in bleeding risk according to commonly used laboratory results, including platelet count and prothrombin time.…”
Section: Discussionmentioning
confidence: 99%
“…An additional concern with administering plasma is the increased risk for rebleeding due to the increased intravascular pressure caused by the volume transfused, particularly among patients with advanced portal hypertension and esophageal varices. 44,81 85 During the perioperative period in liver transplant recipients, transfusion of any plasma or >4 U packed red bold cells (PRBCs) 86 or platelets 87 is associated with decreased short-term transplant survival.…”
Section: Methodsmentioning
confidence: 99%
“…43 Blood product transfusions are associated with transfusion-transmitted infections, febrile and allergic reactions, transfusion-associated circulatory overload, transfusion-related acute lung injury, and elevated portal pressures in patients with cirrhosis. 44,81 85…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Patients with severe liver disease have a greater risk of bleeding. In cases involving gastrointestinal bleeding, coagulopathies (Tripodi & Mannucci, 2011), gastrointestinal procedures (Yates et al, 2016) or liver transplantation (Choi et al, 2016), transfusions are often needed, and adverse transfusion reactions (AR) may occur in these recipients.…”
Section: Dear Sirmentioning
confidence: 99%